Analisis Faktor Yang Mempengaruhi Efisiensi Penggunaan Tempat Tidur Berdasarkan Grafik Barber Johnson di RSU Bunda Margonda - Santi Lestari; Nuha Aqya Ramadhan (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The efficiency of hospital bed utilization is commonly evaluated using four key performance indicators: Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), and Bed Turn Over (BTO). These indicators are then assessed comprehensively through the Barber Johnson Chart to determine overall inpatient service efficiency. Based on the 2024 inpatient service records of Bunda Margonda General Hospital, the BOR reached 91.01%, AvLOS was 3.47 days, TOI was 0.34 days, and BTO was 95.87 times—values that generally fall outside the recommended efficiency thresholds. This study aims to identify the factors contributing to the inefficiency of bed utilization using Barber Johnson indicators throughout 2024. A quantitative analytical approach with a cross-sectional design was employed, utilizing secondary data derived from the annual inpatient census. The analysis compared each indicator with the Barber Johnson standards and examined inefficiency patterns across monthly variations and individual care units. The findings reveal that BOR and BTO were substantially above the optimal range, TOI was lower than the recommended standard, while AvLOS remained within acceptable limits. When plotted on the Barber Johnson Chart, the combined indicators positioned the hospital outside the designated efficiency zone, indicating suboptimal bed utilization performance.